Vincent Van Gogh matters of identity - Vasseur, Yves (Mercatorfonds, 2020)
"During a press conference at the Van Gogh Museum in Amsterdam in November 2018, the author of this book revealed that one of the two know photographs of the painter Vincent van Gogh was in fact of his brother Theo. The series of events that led to this unexpected discovery is full of yet-unpublished anecdotes, fascinating encounters and twists worthy of a thriller."--back cover
Keywords: Gogh, Vincent van -- 1853-1890; Gogh, Vincent van / 1853-1890 / Portraits; Gogh, Theo van / 1857-1891 / Portraits; Mistaken identity; Art criticism; Art / Expertising; Erreur sur la personne; Critique d'art; Art / Expertise; art criticism; connoisseurship; Gogh, Theo van / 1857-1891; Gogh, Vincent van / 1853-1890; Portraits